Spatial heterogeneity of precursory accelerating deformation in uniaxially compressed sandstones and prediction of failure time - Cheng, L.; Hao, S.; Lu, Chunsheng (2024)
The power law acceleration has been validated as an effective method for predicting failure time, however, the precursory acceleration distribution in local monitoring signals is still unclear. In this paper, the spatial distributions of precursory acceleration of strains at different positions and in various size windows are reported based on surface strain fields measured from sandstone. The sandstone specimens are uniaxially compressed and a digital image correlation technique is applied to monitor the evolution of surface strain fields. The precursory acceleration of strains exhibits heterogeneities in amplitudes and durations, which are related to the evolution of strain localization in a higher strain zone. Strain rates at higher strain zones are prone to acceleration. There exists a well-defined size for monitoring and identifying the precursory acceleration of strains. In the vicinity of failure, strain accelerations in different positions and various size windows are described by a power law behavior with a constant exponent. The results show that prediction is stable and agrees well with the actual failure time.